2016
DOI: 10.1016/j.jjcc.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Implantation depth measured by 64-slice computed tomography is associated with permanent pacemaker requirement following transcatheter aortic valve implantation with the Core Valve ® system

Abstract: Implantation depth of the Core Valve(®) into the LVOT was associated with post-procedural PM requirement. Thereby, a cut-off value of 6mm, as measured by 64-slice CT, proved useful to define patients at risk for PM requirement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In our study, the most commonly used prosthesis types were associated with a decreasing PM implantation rate over the years of experience. Although current studies reported that PM implantation after TAVI depends on the implantation depth of the prosthesis [18,21,22], varying implantation depth in order to decrease conduction disturbances after TAVI has not been pursued at our heart center. Furthermore, we did not change implantation strategy but evaluated the measurement of the anulus by computer tomography instead of early rotational angiography in addition to transesophageal echocardiography which is more precise to define optimal size of the prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the most commonly used prosthesis types were associated with a decreasing PM implantation rate over the years of experience. Although current studies reported that PM implantation after TAVI depends on the implantation depth of the prosthesis [18,21,22], varying implantation depth in order to decrease conduction disturbances after TAVI has not been pursued at our heart center. Furthermore, we did not change implantation strategy but evaluated the measurement of the anulus by computer tomography instead of early rotational angiography in addition to transesophageal echocardiography which is more precise to define optimal size of the prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In people where the AV nodal conduction tract is damaged or mechanically affected by aortic valve surgery, pacemaker implantation may be needed [ 32 , 33 , 34 ]. The implantation of a permanent pacemaker for therapeutic purposes in various brady-arrhythmias is now also an option in horses and could potentially have been applied in this case as well [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high risk of AV node or left bundle branch alteration with the Lotus valve is most likely caused by its high radial force in combination with a deep initial valve deployment in the LVOT, according to instruction for use. Since the implantation depth appears to be an important risk factor for PPI also with other nitinol-framed THVs [29], iterations of the next generation Lotus delivery systemincluding the depth guard to prevent deep initial expansionmight improve this limitation.…”
Section: Permanent Pacemaker Implantationsmentioning
confidence: 99%